A conceptual framework to examines brand equity in bank and financial firms - Suyono Saputra (Management Department, Faculty of Economics and Business, Universitas Jambi, 2020)
In this study, the conceptual framework of brand equity is a combination of antecedents that create differential effects to customer response on customer-based brand equity in the banking and financial industry in Batam. By constructing a conceptual framework of the factors affecting brand equity, company will build a competitive advantage in the banking and financial industry that will increase their long-term sustainability in Batam. The recent trends of banking industry have changed tremendously, and studies of a brand equity in the banking industry at Batam and Indonesia is increasingly becoming considerable to keep pace with this change. In this conceptual paper, we have summarized the literatures on currently prevailing concepts and approaches on brand equity that will allow us to identify the conceptual framework of brand equity including all the factors affecting the customer response namely brand image, brand loyalty, brand awareness, and perceived quality and therefore will facilitate banking and financial firms to enhance their marketing efficiency and effectiveness in Batam.